Research in substance abuse treatment: Contributions by the Centre for Alcohol and Drug Research. (December 2013) - Pedersen, Mads Uffe; Hesse, Morten; Thylstrup, Birgitte
<x xml:space="preserve">Abstract</x> This article describes contributions from the Centre for Alcohol and Drug Research (CRF), Faculty of Business and Social Sciences, Aarhus University, within treatment for alcohol and drug problems. This article focuses on three key research areas: evaluation research and development of monitoring systems/registers, development of screening and treatment methods, and treatment system research. Some of the important findings from the studies conducted within these three areas will be presented and the impact that these findings have had on Danish treatment policy will be described.